Layanan Bimbingan dan Konseling Pribadi Sosial - Hidayat, Arifin (Jurnal Al-Irsyad: Jurnal Bimbingan Konseling Islam, 2019)
Every individual has a problem that must be resolved with various types of services according to the problem at hand. Many of the problems faced include personal and social problems. Personal social problems include the inability to understand themselves and others. Not infrequently the problems faced by individuals affected by others. Therefore need assistance in the form of guidance and counseling services specifically for the private and social fields. This study aims to explain the comprehensive personal and social counseling guidance service as a guide for teachers and counselors in using this service. The research method used is literature study, which is gathering various information relevant to the object of research. Starting from books to journals related to this research. The findings in this study, that social counseling and guidance services are carried out to restore the counselee to be an independent person capable of understanding and accepting themselves and others, and able to adapt to their social environment. Problems found in the social person are: interaction relationships with other people (parents, siblings, friends, teachers and the community in the individual environment), problems in self-regulation both in the spiritual field, self-care (physical and spiritual), conflict resolution and so. While the services provided are individual counseling, consultation, advice, group guidance, group counseling, remedial teaching, teaching nuances of guidance.